Analysis Students' Misconception in Optical Material Using Three Tier Multiple Choice Diagnostic Test - Sri Lestari Handayani; Arifin Arifin (Physics Education Research Journal, 2021)
This study aims to analyze the misconceptions of Senior High School students and their cause in Optical material. The data collection techniques used in this research are tests and interviews. The three tiers multiple-choice diagnostic test used consists of three levels, the first is a question, the second is the reason for the answer, and the third is the student's confidence level.  The data analysis techniques used in this research are multiple-choice scoring analysis without fining and student's misconceptions level's percentage analysis. The lowest misconception level is 10.4% on the light refraction indicator, and the highest is 41.6% on the distance and characteristic of the image on the concave mirror. The sources of students' misconceptions found in this study are the students themselves, books, friends, teachers, students' daily experiences, and the Internet.